PERANCANGAN SEQUENCE DAN SCHEDULLING PENAMBANGAN BATUBARA DI PT. ALLIED INDO COAL JAYA, PARAMBAHAN, DESA BATU TANJUNG, KECAMATAN TALAWI, KOTA SAWAHLUNTO, SUMATERA BARAT - Muhammad Al Fajri Tamsin; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Allied Indo Coal Jaya is one of the companies engaged in Coal mining with an IUP covering an area of 327.40 Ha, in actual mining activities using the Open Pit method with a production target in 2021 of 278,000 MT of Coal , suddenly the company decided to increase the production target in 2022 by 404,000 MT for the Open Pit so that a re-mine planning is needed to support production activities in 2022 and beyond, the mine Design begins by calculating the Volume of Overburden and Coal contained in the mining boundary area so that a Resgraphic is obtained which is useful for Designing Pit Limit., then this Pit Limit is the economic limit of mining, then the annual Sequence Design is carried out according to the company's production target in the next 3 years, making the Sequence using the sequential method, namely to Mining activities are carried out simultaneously in certain areas with different elevations. In Year 1, total OB production was 5,179,135.9 BCM and total Coal production was 251,748 MT with a total effective working hour of 2,520 hours. In Year II mining, the acquisition of OB was 5,116,000 BCM and Coal was 401,000 MT. Likewise with Mining Year III where the acquisition of OB is 5,093.00 and Coal is 401,000,. In the above annual Design, the total Volume of Overburden is 15,371,000 BCM and the amount of Coal is 1,201,000 MT, so that the remaining vs. 3,524,043 BCM for OB and about 219,976.7 MT of Coal .